Durability Properties of High Volume Slag and Slag-Fly Ash Blended Concrete Containing Nano materials - Hosan, Md Anwar (Curtin University, 2020)
This research investigated the effect of the addition of a small amount of nano silica and nano calcium carbonate on the compressive strengths and durability properties of high volume slag (HVS) and high volume slag-fly ash (HVS-FA) blended concretes. The results showed that low-carbon concretes containing 70% blast furnace slag or 70% slag-fly blended materials with superior strengths and durability can be achievable by adding only 1% nano calcium carbonate and 2-3% nano silica.